2010
DOI: 10.1021/jf903614d
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Intracellular pH in Human Stomach Cells: A Novel Approach To Evaluate the Gastric Acid Secretory Potential of Coffee Beverages

Abstract: As the consumption of coffee beverages sometimes is reported to cause gastric irritation, for which an increased stomach acid secretion is one of the promoting factors, different processing technologies such as steam-treatment have been developed to reduce putative stomach irritating compounds. There is evidence-based data neither on the effect of detailed processing variations nor on individual coffee components affecting the proton secretory activity (PSA). This work aimed at developing a screening model sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 30 publications
1
60
1
Order By: Relevance
“…Study coffee characteristics Concentrations of thermally labile green coffee bean constituents, such as CQAs (580 mg/L) in the study coffee brew were slightly lower than those reported in the literature for commercial filter coffee [7]. The concentrations of NMP (72 mg/L) were in the upper range of dark roasts [5].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Study coffee characteristics Concentrations of thermally labile green coffee bean constituents, such as CQAs (580 mg/L) in the study coffee brew were slightly lower than those reported in the literature for commercial filter coffee [7]. The concentrations of NMP (72 mg/L) were in the upper range of dark roasts [5].…”
Section: Introductionmentioning
confidence: 62%
“…The coffee was freshly brewed in a conventional coffee filter machine immediately before each individual 250-mL consumption. The coffee brew was analytically characterized using HPLC-DAD and HPLC-MS/MS [7] (Supporting Information, preparation and analysis of the coffee brew studied).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were set to a concentration of 1 Â 10 6 viable cells per milliliter of PBS. The gastric acid secretory acitvity of the cells was measured by the determination of the intracellular proton index (IPX) using the fluorescence dye carboxy-SNARF-AM as a probe for the measurement of the intracellular pH value (29). HGT-1 cells were loaded with the dye (3 μmol/L) for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of the present investigation was, therefore, to develop a sensitive HPLC-MS/MS method enabling the accurate and reliable quantitative analysis of β N-alkanoyl-5-hydroxytryptamides in coffee beverages by means of a stable isotope dilution analysis, and to evaluate the activity of these compounds on gastric acid (GA) secretion by using an in vitro HGT-1 cell assay, which has recently been developed and successfully applied to assess the GA secretion induced by coffee beverages (29).…”
Section: Introductionmentioning
confidence: 99%
“…The coffee samples were analytically characterized using highperformance liquid chromatography diode array detector (HPLC-DAD) and liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) methods previously described. Caffeine and CQA were quantified by HPLC-DAD (324, 272 nm) with external calibration [23]. NMP and trigonelline in coffee were quantified by stable isotope dilution analysis with synthetic d 3 -NMP after sample cleanup via solid-phase extraction (SPE) on RP18 [24].…”
Section: Study Coffeementioning
confidence: 99%